2015
DOI: 10.1039/c5ra00450k
|View full text |Cite
|
Sign up to set email alerts
|

Morphology development of PP/POE blends with high loading of magnesium hydroxide

Abstract: The influence of high loading magnesium hydroxide (Mg(OH) 2 , MDH) on the morphology and properties of the polypropylene (PP)/ethylene-octene copolymer (POE) blends has been investigated via scanning electron microscopy, dynamic mechanical thermal analysis and tensile mechanical testing. It was demonstrated that the mechanical properties, especially the elongation at break, are highly related to the phase structure exhibited by the composites. In the PP/POE 90/10 and 70/30 blends, the addition of a high 10 loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Table 7 and Figure 2 report the results of tests obtained on composites produced using the 3 wt.% of coupling agent and varying the n-MDH dosage in the range between 56 wt.% (33.8 vol.%) and 64 wt.% (41.6 vol.%), aimed to find the required amount of filler for providing the best trade-off between good flame retardant properties (expressed by Limited Oxygen Index LOI, usually >32 %O2 [30,31]) and adequate mechanical properties required for cable application (i.e., tensile strength >10 MPa and elongation at break >150% [23]). Notably, tensile strength and elongation at break are both enhanced by increasing the dosage of the coupling agent thanks to the double effect provided by the compatibilizing grafted MAH groups and the flexibility conferred by the ULDPE matrix [29].…”
Section: Variation Of Content Of N-mdhmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 7 and Figure 2 report the results of tests obtained on composites produced using the 3 wt.% of coupling agent and varying the n-MDH dosage in the range between 56 wt.% (33.8 vol.%) and 64 wt.% (41.6 vol.%), aimed to find the required amount of filler for providing the best trade-off between good flame retardant properties (expressed by Limited Oxygen Index LOI, usually >32 %O2 [30,31]) and adequate mechanical properties required for cable application (i.e., tensile strength >10 MPa and elongation at break >150% [23]). Notably, tensile strength and elongation at break are both enhanced by increasing the dosage of the coupling agent thanks to the double effect provided by the compatibilizing grafted MAH groups and the flexibility conferred by the ULDPE matrix [29].…”
Section: Variation Of Content Of N-mdhmentioning
confidence: 99%
“…Among the listed polymers, those based on VLDPE and mLLDPE (low density polyethylene copolymers based on octene, hexene, or butene obtained through metallocene catalysts) are preferred, being helpful for the elongation at break and primarily on the workability during processing. ULDPE (ethylene α-olefin copolymer) and C 3 -C 2 copolymers, produced with both metallocenic and Ziegler-Natta catalyst, result the most preferred since the more amorphous character and long chain branching better withstand high percentages of fillers [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Variation Of Type Of Polyolefin Used In Combination With Eva28mentioning
confidence: 99%
See 2 more Smart Citations
“…5,8 In recent years, ethylene-octene copolymer (POE) has attracted much industrial interest as an excellent impact modifier and proved more effective in toughening iPP due to lower interfacial tension and better compatibility between POE and iPP and easier processability than other elastomers, and is gradually replacing EPR and EPDM in iPP toughening. 7,9 So far, numerous studies have been carried out on the miscibility, mechanical properties, morphology and microstructure of iPP/POE blends. It was reported that iPP and POE are partially miscible and their blends usually exhibit a two-phase morphology.…”
Section: Introductionmentioning
confidence: 99%